2012
DOI: 10.5424/fs/2112211-11463
|View full text |Cite
|
Sign up to set email alerts
|

Stand, tree and crown variables affecting cone crop and seed yield of Aleppo pine forests in different bioclimatic regions of Tunisia

Abstract: In Tunisia, the Aleppo pine seed has a great importance, since in the last decades human consumption has risen considerable. Thus its regeneration and seed production capacities are important factors to take into account to reach the necessities of the country. To study the production of cones and seeds of Aleppo pine, Tunisia's native Aleppo pine forests were surveyed in summer 2006, using 79 plots (40 × 25 m: 1,000 m²) spread over four bioclimatic zones. Stand and tree characteristics, crown dimensions and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
3
13
1
Order By: Relevance
“…As indicated in Fig. 2, this allocation is influenced by local stand density as well as other practices like pruning (Ayari et al 2012). Thinning and pruning also affect the plasticity, which will interact with selection processes as previously mentioned: The question here is whether the plastic response induced by the silviculture is adaptive or maladaptive regarding future climate change.…”
Section: Foreseen Evolutionary Impact Of Common Forestry Practicementioning
confidence: 99%
“…As indicated in Fig. 2, this allocation is influenced by local stand density as well as other practices like pruning (Ayari et al 2012). Thinning and pruning also affect the plasticity, which will interact with selection processes as previously mentioned: The question here is whether the plastic response induced by the silviculture is adaptive or maladaptive regarding future climate change.…”
Section: Foreseen Evolutionary Impact Of Common Forestry Practicementioning
confidence: 99%
“…Some studies have observed that cone production by Pinus spp. (Pinus halepensis and Pinus sylvestris) is not uniform and often varies among compartments within the crown (Ayari et al, 2012;Abdelaziz Ayari and Khouja, 2014;Iwaizumi et al, 2008). These variations are considered to be associated with resource-related factors such as collection practices, crown size, stand density, and light intensity (Iwaizumi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We found that basal area is positively correlated with pine production in this sense. Ayari et al (2011aAyari et al ( , 2012a, Mencuccini et al (1995) and Arista and Talavera (1996) showed that basal area had a positive influence on seed and cone productions (Tunisia, Italy, Spain). Ayari et al (2011c) showed that the seed and cone productions increased with an increase in tree height, DBH and age (Tunisia).…”
Section: Discussionmentioning
confidence: 99%
“…Goubitz et al (2004), Moya et al (2008b) and Verkaik and Espelta (2006) found that the level of cone serotiny decreased with an increase in tree height (Israel, Spain). Ayari et al (2012a), Girard et al (2012) and Malcolm et al (2001) showed that the seed and cone productions increased with an increase in tree crown height and tree crown diameter (Tunisia, France). Dendrometric measurements have been confirmed as easier and less costly estimators for Aleppo pine forests in the southern Mediterranean Basin, which have been described as more vigorous in growth and fruiting than the northern or eastern Mediterranean populations (Climent et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation